Establishing a novel assay system for measuring renin concentration using cost effective recombinant ovine angiotensinogen. Issue 4 (April 2019) - Akther, Jobaida; Nabi, A.H.M. Nurun; Ohno, Satoshi; Yokogawa, Takashi; Nakagawa, Tsutomu; Suzuki, Fumiaki; Ebihara, Akio
Abstract: Background: Plasma renin can predict future cardiovascular events as well as the prevalence of chronic renal disease in hypertensive subjects. Ovine angiotensinogen (oANG) is a better substrate for measuring renin concentration through activity assay. Recombinant oANG expressed in Escherichia coli cells can be utilized as the substrate while measuring plasma renin. We aim to establish an immunoassay for measuring renin concentration at picomolar level using recombinant oANG. Material and methods: Recombinant oANG was expressed in E. coli cells and purified to homogeneity. Various concentrations (0–1.5 pM) of recombinant human renin standard were prepared and incubated with recombinant oANG. Renin activity was determined by angiotensin-I specific enzyme-linked immunosorbent assay. Results: About 4.5 mg of purified recombinant oANG was obtained from 0.5 L of E. coli culture. The Michaelis constant and turnover number of human renin with recombinant oANG were 0.16 μM and 0.51 s −1, respectively. A linear relationship was obtained when renin activity was plotted as a function of renin concentration using recombinant oANG as the renin substrate. Picomolar amounts of renin can be measured from known renin activity using this method. Conclusion: This study established a novel assay system for measuring renin at picomolar level using cost effective recombinant oANG.